Evaluasi, perubahan dan kontinuitas kebijakan: studi kasus kebijakan Pilkada serentak 2020 di Bandar Lampung - Anintya, Veronika Frisda; Rantika, Senja; Fitriyani, Yasintha; Arismunandar, Firsty Yusdanissa; Zakiyah, Sabila (Jurnal Studi Ilmu Sosial dan Politik, 2021)
Purpose: Regional Head Election (Pilkada) is a democratic party where the people directly and democratically elect the Governor and Deputy Governor, the Regent and Deputy Regent, as well as the Mayor and Deputy Mayor in the province and district/city. However, there is a slight difference between the implementation of the purpose of writing this journal is to evaluate and find out the changes and continuity of policies of the Bandar Lampung City Government about the simultaneous Pilkada un the middle of the Covid-19 pandemic. Research methodology: The method uses quantitative research by using a questionnaire for sampling to vote with Google Form software. Results: The study results are most people already know about the changes in policy and implementation of health protocols in the regional head elections is non-voting and evaluation less than optimal. Limitations: In this study, the authors have limitations, namely in the form of limited time in distributing questionnaires. Contribution: This research can be used throughout Indonesia, especially in the Bandar Lampung City. Keywords: Regional Head Election, Covid-19, Policy evaluation